1990
DOI: 10.1177/0022022190211001
|View full text |Cite
|
Sign up to set email alerts
|

International Preferences in Selecting Mates

Abstract: This study sought to identify the effects of culture and sex on mate preferences using samples drawn world-wide. Thirty-seven samples were obtained from 33 countries located on six continents and five islands (N = 9,474). Hierarchical multiple regressions revealed strong effects of both culture and sex, moderated by specific mate characteristics. Chastity proved to be the mate characteristic on which cultures varied the most. The preference ordering of each sample was contrasted with an international complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
468
3
36

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 632 publications
(551 citation statements)
references
References 10 publications
44
468
3
36
Order By: Relevance
“…Os resultados também evidenciam a relevância de se considerar a variável sexo para compreender tanto a importância diferenciada que as pessoas dão aos atributos do/a parceiro/a ideal como conhecer em que medida esta pode estar correlacionada com os valores humanos. Estudos já apontavam a diferença entre os sexos no que se refere à escolha do parceiro ideal (Buss,1989;Buss et al, 1990;Féres-Carneiro, 1997). Corroborando pesquisas prévias, constatou-se que as mulheres valorizam mais a dimensão social (Silva et al, 2005); os homens valorizam mais do que as mulheres a aparência física (Féres-Carneiro, 1997;Silva et al, 2005).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Os resultados também evidenciam a relevância de se considerar a variável sexo para compreender tanto a importância diferenciada que as pessoas dão aos atributos do/a parceiro/a ideal como conhecer em que medida esta pode estar correlacionada com os valores humanos. Estudos já apontavam a diferença entre os sexos no que se refere à escolha do parceiro ideal (Buss,1989;Buss et al, 1990;Féres-Carneiro, 1997). Corroborando pesquisas prévias, constatou-se que as mulheres valorizam mais a dimensão social (Silva et al, 2005); os homens valorizam mais do que as mulheres a aparência física (Féres-Carneiro, 1997;Silva et al, 2005).…”
Section: Discussionunclassified
“…Em pesquisa realizada em 37 culturas sobre a escolha do parceiro ideal para fins de casamento ou relação duradoura, Buss (1989;Buss et al, 1990) encontrou diferenças entre os gêneros. Constatou que as mulheres tendem a valorizar mais do que os homens a capacidade de ganho material.…”
Section: Relações Entre Casais E Atributos Desejadosunclassified
See 2 more Smart Citations
“…Physical attractiveness is a primary determinant of the extent to which one is perceived as a desirable mate (Buss et al, 1990;Fletcher, Kerr, Li, & Valentine, 2014;Schwarz & Hassebrauck, 2012), and one of the most important aspects of male physical attractiveness is upper body "V-shapedness." Several studies have shown that men with more V-shaped upper bodies are perceived as more attractive (Braun & Bryan, 2006;Brown et al, 2008;Horvath, 1979;Maisey, Vale, Cornelissen & Tovée, 1999;Price, Pound, Dunn, Hopkins, & Kang, 2013;Swami & Tovée, 2005;Swami et al, 2007).…”
mentioning
confidence: 99%